Probabilistic Approach for Identifying Longest Fuzzy Critical Path - Z. Ahmood, Ranen; N. Abdulahad, Fedaa (Al-Nahrain Journal of Science, 2022)
This paper, considers the occurring problem of fuzzy project network either in some or whole activities which are interrupted. A probability density function is constructed from the activities of the membership of the fuzzy set. Then an approach is proposed for identifying the longest critical path, by determining in each activity the criticality index depending on the costs yielded from project lateness caused by the interruption activities. A case study is presented and simulated to explain our approach.